Uma ameaça à liderança estadunidense : uma análise da política externa dos Estados Unidos em relação à China (1990-2020) - Eduardo Melo Vidal (2023)
The rapid rise of China between 1990 and 2020 was accompanied by a significant shift in the United States' perception of China itself, which, in turn, generated a substantial change in Washington's foreign policy towards Beijing. The aim of this dissertation is precisely to analyze this transition in the conduct of US foreign policy. Therefore, we opted for the development of a structured narrative based on the basic precepts of Process Tracing, in order to understand, through the lens of Neoclassical Realism, the mechanisms connecting China's rise to the change in American foreign policy. The four chapters addressed the historical and theoretical context, highlighted the established US leadership and the rise of China, and discussed the evolution of American foreign policy towards China over the last decades, based on presidential speeches and official documents. The analysis revealed that China shifted on a scale of US foreign policy priorities. Over thirty years, the Asian country transitioned from just another foreign policy agenda to a threat to US leadership. Although the Trump administration catalyzed tensions with China, this process began with his predecessors and was gradually built over the course of three decades, stemming from China's rise and the US perception of what this rise signified.